Public Perception on the Role of Kiai in Yogyakarta - Marmiati Mawardi (Analisa: Journal of Social Science and Religion, 2013)
This paper is a summary of the research conducted in the province of Special Region of Yogyakarta, and put people in the Yogyakarta City, Sleman Regency and Kulonprogo Regency as sample. This research aimed to discribe people’s perception of the of kiai (Islamic scholars) in the field of empowerment for improving the quality of religious life and increasing religious harmony in Special Region of Yogyakarta. The analysis results showed that the kiai has considerable role for improving the religious diversity among community and improve the quality of religious harmony. The public view on the dimension of beliefs, rituals and social very negative an relatively small. This reality showed that Yogyakarta people’s religious knowledge was quite diverse, so there is a different perception. People’s perception of the role of kiai in improving the quality of religious life and religious harmony based on the social background of respondents of all categories, respondents said that kiai have positive role.